A comparison of three spermatozoa selection techniques for Intracytoplasmic Sperm Injection (ICSI) using swim-up, Cumulus Oophorus Model and PICSI ® Dish - Rijsdijk, Michelle (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University 2015.